SUGAR SWEETENED BEVERAGE TAX AND ITS IMPLICATIONS FOR PUBLIC HEALTH - Anugraha John; Sinthu Sarathamani Swaminathan; Hari Teja Avirneni (Universitas Airlangga, 2023)
Introduction: Sugar Sweetened Beverages (SSBs) consumption has increased to higher levels across all corners of the world. High sugar diets in the form of SSBs lead to increased calorie intake with almost no nutritive value when compared to solid food and contributes to the increased energy intake resulting in an unhealthy weight gain, often associated with health issues such as obesity, diabetes, cardio-vascular diseases, early tooth decay and formation of cavities. It is also observed that consumption of SSBs is linked to unhealthy habits like smoking, decreased physical activity, increased intake of fast food and increased screen time. Method: The required information on SSB tax implementation at the global level was retrieved from the literature reviews. Result: Taking such detrimental effects of SSBs into consideration, many countries are putting efforts to tackle the problem of higher consumption of SSBs by adopting measures such as taxations on SSBs. However, it is also extremely important to understand how these taxes help in generating higher revenues to the government which, in turn, can be used for various community needs in the respective countries. Conclusion: The same revenue can also be utilised for implementation of comprehensive healthcare programmes especially in Low and Middle-Income Countries (LMIC), by providing preventive, promotive, curative, rehabilitative and palliative services as a way to progress towards Universal Health Coverage (UHC).